2005
DOI: 10.1016/j.jcrs.2005.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Blue-light filtering intraocular lens in patients with diabetes: Contrast sensitivity and chromatic discrimination

Abstract: In diabetic patients, the AcrySof Natural IOL provides better contrast sensitivity than the AcrySof SA60AT. The blue-light filter of the AcrySof Natural IOL did not cause chromatic discrimination defects based on total error scores and improved color vision in the blue-yellow chromatic axis in diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 39 publications
3
55
2
3
Order By: Relevance
“…The AcrySof ReSTOR Aspheric IOL is manufactured with a material which includes a bluelight-absorbing chromophore designed to approximate more closely the light-transmittance characteristics of the natural lens at wavelengths below approximately 500 nm. It has been shown that the use of this blue-light filter would be more advisable because it avoids retinal ultraviolet light alterations without disturbance of CS 12,13 and chromatic vision 15,16 .…”
Section: Methodsmentioning
confidence: 99%
“…The AcrySof ReSTOR Aspheric IOL is manufactured with a material which includes a bluelight-absorbing chromophore designed to approximate more closely the light-transmittance characteristics of the natural lens at wavelengths below approximately 500 nm. It has been shown that the use of this blue-light filter would be more advisable because it avoids retinal ultraviolet light alterations without disturbance of CS 12,13 and chromatic vision 15,16 .…”
Section: Methodsmentioning
confidence: 99%
“…The IOL material includes a blue light-filtering chromophore. It has been shown that the use of a blue-light filter is advisable because it prevents ultraviolet light alterations to the retina without disturbing CS and chromatic vision (28,29) .…”
Section: Iol Specificationsmentioning
confidence: 99%
“…Authors have studied visual performance under mesopic and photopic conditions [46], and have defined which IOL provides better contrast sensitivity in diabetic subjects [47][48][49] On the other hand, studies of pupillary responses have been done in health and diabetic subjects [18,50]. Also ANOVA test is a helpful tool in optometric studies [51][52].…”
Section: Anova To Analyze Pupillary Variations In Pseudophakic Eyes mentioning
confidence: 99%